ANALISIS KEBUTUHAN BAHAN AJAR TOPIK ANIMALIA KELAS X SMA/MA (Jurnal Bioconcetta, 2022)
AbstractLearning outcomes of Animalia grade X of Senior High School required students to have the ability to group animals into phyla based on body layers, body cavities, and body symmetry as well as reproduction and relate their role in life. for the learning requirements of the Animalia topic to be identified, observations and analyses were carried out on the problems of teachers, students, tools, and learning facilities. This research is a descriptive study. The research instruments used were interview questionnaires, book content analysis questionnaires, and literature studies. the data obtained were analyzed descriptively. Based on the results of interviews with biology teachers, information was received that the availability of library textbooks was very lacking. From the results of the analysis of the contents of the book, it was found that the explanation has been separated by perphyla but has not explained the classification of Animalia, and has not included its role in life. Analysis of the curriculum content found that the school had used the 2013 revised 2018 curriculum but the learning objectives had not been described by KD 3.9. Based on the analysis results, it has to develop teaching materials that are to student requirements.Â